(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Different numerical approaches to solving ordinary differential equations (ODEs) are compared in this research. It is critical to have a reliable and effective solution for ODEs because of its widespread use in modelling dynamic systems in many branches of science and engineering. Numerous popular numerical methods, such as the Finite Difference method, the Runge-Kutta methods, and Euler’s method, are assessed in this study. We evaluate these strategies’ efficacy according to their precision, computational efficiency, and practicality. This article highlights the merits and limits of each technique via a series of benchmark problems, providing insights into their application to various forms of ODEs. In order to improve the accuracy and consistency of ODE solutions, the results should help in choosing the right numerical approaches for real-world applications.